Mechanical model of errors of probes for numerical controlled machine tools. (January 2016) - Jankowski, Michal; Wozniak, Adam
Highlights: A new mechanical model of errors of probes for CNC machine tools is proposed. The model enables digital compensation of the errors of CNC machine tool probes. The validity of the model is experimentally confirmed using a dedicated setup. Abstract: CNC machine tool probes are not only used to set up the workpiece before machining and to control it after machining, but also to determine volumetric errors of the machine tool. That's why there is a necessity not only for knowledge of the complete on-machine measurement system errors, but also for the knowledge about probe's errors in separation from machine tools. This paper presents a theoretical model of errors of probes for CNC machine tools. It takes into account such unique features of the machine tool probes as the transducer with support on the whole circumference and as wireless communication. 3 probes: RMP60, MP700 and IRP32.00-MINI were tested using moving master artifact method, out of machine tool, to verify the model described. The triggering radius values obtained experimentally were compared with values calculated using theoretical model, resulting with a compliance up to 92%.